1991
DOI: 10.1016/0014-5793(91)81332-3
|View full text |Cite
|
Sign up to set email alerts
|

Diverse proteins homologous to inositol monophosphatase

Abstract: Bovine inositol monophosphatase (IMP) and several homologous proteins were found to share two sequence motifs with bovine inositol polyphosphate I-phosphatase (IPP). These motifs may correspond to binding sites within IMP and IPP for inositol phosphates or for lithium, since both substances are bound by these proteins. This suggests that the proteins homologous to IMP, which have diverse biological roles but whose function is not clear, may act by enhancing the synthesis or degradation of phosphorylated compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 10 publications
1
52
0
Order By: Relevance
“…The evolutionary distances among the representative seven members of the inositol monophosphatase family (26) have been calculated by the method of Hein (13), and the resulting phylogenetic tree is illustrated in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The evolutionary distances among the representative seven members of the inositol monophosphatase family (26) have been calculated by the method of Hein (13), and the resulting phylogenetic tree is illustrated in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…The seven members that were used for calculation included SuhB, bovine inositol monophosphatase (4), CysQ (which is involved in sulfate assimilation in E. coli) (25), Qut-G and Qa-X (which are hypothetical gene products from open reading frames in Aspergillus nidulans and Neurospora crassa, respectively) (8,12), bovine inositol polyphosphate 1-phosphatase (which hydrolyzes the 1-position phosphate of inositol 1,3,4-triphosphate and inositol 1,4-bisphosphate) (41), and Met22 (which is involved in salt tolerance in Saccharomyces cerevisiae) (9). Not only do these proteins share two sequence motifs (26), but the similarity is found throughout the length of the SuhB sequence (except for long insertions in inositol polyphosphate 1-phosphatase, Met22, Qut-G, and Qa-X). Although SuhB and bovine inositol monophosphatase belong to different kingdoms, the phylogenetic analysis showed that SuhB has a close relationship to the mammalian inositol monophosphatases (the overall amino acid identity is approximately 30%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two additional IMP genes were isolated based on their similarity to LelMP7. All of these genes share four domains that are found not only in known IMP proteins but also in several proteins of unknown biochemical function (see Neuwald et al, 1994) as well as in the yeast HAL2 protein, which encodes a bisphosphate nucleotidase that is involved in salt tolerance (Murguia et al, 1995). Expression of the LelMP genes in Escherichia coli confirmed that these genes indeed encode IMPs: all were able to dephosphorylate l%-labeled inositol 1-phosphate.…”
Section: In Thls Issuementioning
confidence: 92%